Die Nachhaltigkeit von geförderten Existenzgründungen aus Arbeitslosigkeit: Eine Bilanz nach fünf Jahren - Marco Caliendo; Steffen Künn; Frank Wießner (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2010)
– One of the main instruments which was introduced with the 'Hartz-Reforms' was a start-up subsidy called Me Inc. ('Ich-AG'). This instrument was introduced in addition to the Bridging Allowance ('Überbrückungsgeld') which had already been implemented in the 1980s. Between 2003 and 2006 more than one million formerly unemployed were supported to set up their own business with these two schemes. Previous studies showed that both programmes rather complemented each other by attracting different target groups to start up their own business. Short- and medium-term prospects of both programmes were already evaluated positively within the evaluation of the 'Hartz-Reforms'; whereas long-term evidence could not be drawn due to the limited observation window. This study closes this research gap and provides evidence on the success of subsidized start-ups five years after foundation. It turns out that about 50 to 60 percent of former Me Inc. founders and 53 to 67 percent of Bridging Allowance participants are still full-/part-time self-employed at this time. With respect to labour market integration both schemes can be considered as effective: Throughout, we find higher employment rates for participants in comparison to other non-subsidized unemployed individuals; participants additionally achieve higher incomes. The induced employment effects are relatively high for the Bridging Allowance scheme; for each 100,000 supported start-ups 80,000 additional full-time equivalents have been created.
Keywords: J68; M13; H43; C14; 330; Existenzgründungszuschuss - Erfolgskontrolle; Überbrückungsgeld - Erfolgskontrolle; Unternehmensgründung - Förderung; Ich-AG; Unternehmenserfolg; berufliche Selbständigkeit - Dauer; Einkommenshöhe; geschlechtsspezifische Faktoren; Westdeutschland; Ostdeutschland; Bundesrepublik Deutschland